2004
DOI: 10.1111/j.1423-0410.2004.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of latent human cytomegalovirus by conventional gamma irradiation and prevention by treatment with INACTINE PEN110

Abstract: These results demonstrate that gamma irradiation, at levels currently used to treat RCC, has the capacity to induce expression of CMV, whereas PEN110 inhibits CMV replication and efficiently inactivates the infected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…[12,24,1,35] Researchers have shown that ionizing radiation is a risk factor for gliomas and that latent HCMV infection can be reactivated by exposure to radiation. [26] In our laboratory, we found that lymphocytes infected with HCMV exhibit chromosomal instability at levels equal to or above that seen in lymphocytes subjected to gamma irradiation. In addition, we have observed that HCMV increases the sensitivity of lymphocytes to the effects of radiation, leading to greater instability than that in lymphocytes treated with either HCMV or radiation individually.…”
Section: Discussionmentioning
confidence: 93%
“…[12,24,1,35] Researchers have shown that ionizing radiation is a risk factor for gliomas and that latent HCMV infection can be reactivated by exposure to radiation. [26] In our laboratory, we found that lymphocytes infected with HCMV exhibit chromosomal instability at levels equal to or above that seen in lymphocytes subjected to gamma irradiation. In addition, we have observed that HCMV increases the sensitivity of lymphocytes to the effects of radiation, leading to greater instability than that in lymphocytes treated with either HCMV or radiation individually.…”
Section: Discussionmentioning
confidence: 93%
“…12,16,31 In 1 study, g-irradiated blood of unknown CMV status was used, 25 although this method does not inactivate CMV and may even increase CMV replication in latently infected cells. 32 Three studies did not mention any attempt to prevent or identify CMV transmission through transfused blood products. [13][14][15] In 2 studies, infants were prophylactically treated with intravenous Ig.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…To regularly produce an attenuated live vaccine against babesiosis and in order to minimize the risk of viruses being introduced into an animal or animal population directly by the vaccination procedure, it would be advisable to use gamma irradiation of the substrate. However, it is important to recall that some viruses may become activated, such as that reported for human cytomegalovirus (HCV) after gamma irradiation 28 . Another study describes the difficulty for using radiation on HIV sterilization, and concluded that gamma irradiation should be disregarded as a significant virus inactivation method for bone allograft, as the irradiation dose required to achieve a sterility assurance level is 89 kGy, which exceeds current recommendations 29 …”
Section: Discussionmentioning
confidence: 99%